2003
DOI: 10.1073/pnas.1133426100
|View full text |Cite
|
Sign up to set email alerts
|

Insig-1 “brakes” lipogenesis in adipocytes and inhibits differentiation of preadipocytes

Abstract: We have examined gene expression in the fat tissue of normal mice at the onset of diet-induced obesity. Insulin-induced gene 1 (insig-1) mRNA rose progressively with a high-fat diet and declined on a restricted diet. Because insig-1 binds sterol regulatory element-binding protein cleavage-activating protein in the endoplasmic reticulum, thereby blocking proteolytic processing required for sterol regulatory element-binding protein activation, we tested its influence on lipogenesis. In differentiating 3T3-L1 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
83
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 16 publications
13
83
0
1
Order By: Relevance
“…adipose, skeletal muscle and pancreatic beta cells, may influence glucose homeostasis. Thus, in agreement with other studies [29,30], it is feasible that the effect of INSIG1 on adipocyte metabolism is the primary cause of the observed relationship between the −169C>T polymorphism in INSIG1 and glucose homeostasis. In short, more detailed analysis of the role of INSIG1 in the metabolism of hepatic and extra-hepatic tissues will be required to resolve the mechanism of action of INSIG1 in glucose homeostasis.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…adipose, skeletal muscle and pancreatic beta cells, may influence glucose homeostasis. Thus, in agreement with other studies [29,30], it is feasible that the effect of INSIG1 on adipocyte metabolism is the primary cause of the observed relationship between the −169C>T polymorphism in INSIG1 and glucose homeostasis. In short, more detailed analysis of the role of INSIG1 in the metabolism of hepatic and extra-hepatic tissues will be required to resolve the mechanism of action of INSIG1 in glucose homeostasis.…”
Section: Discussionsupporting
confidence: 76%
“…First, DeBose-Boyd and co-workers have reported that INSIG1 is directly involved in the ubiquitination and degradation of 3-hydroxy-3-methylglutaryl-CoA reductase [27,28], a process that is independent of INSIG1-SCAP interaction and activation of the SREBP pathway. Second, Unger and co-workers have provided evidence for a role of INSIG1 in diet-induced obesity [29] and demonstrated that Insig1 expression restricts lipogenesis in mature adipocytes and blocks differentiation in preadipocytes [30]. The present study provides another example of the multifunctional role of INSIG1, and presents evidence that INSIG1 is implicated in the regulation of the plasma glucose concentration in humans.…”
Section: Discussionmentioning
confidence: 69%
“…In addition to the eNOS gene, chromosome 7q36 contains a few other genes that are plausibly implicated in the atherogenic pathway because of their functional significance, for example, insulin-induced gene 1 (154. 48 -154.49 Mb; MIM 602055) (45), protein kinase, AMP-activated, 2 noncatalytic subunit (MIM 602743), and fatty acid binding protein 5-like 3 (46). It is possible that the association we found for the intron 8 locus is the result of linkage disequilibrium with certain SNPs in genes within this area.…”
Section: Discussionmentioning
confidence: 63%
“…(Fig.1) (6). Considering that INSIG-1 appears to inhibit lipo-and adipogenesis, it is hard to reconcile this observation with the pro-adipogenic role of PPAR (9).…”
Section: Transcriptional Regulation Of Lipogenesis In Adipose Tissuementioning
confidence: 81%